Topiramate and Cognitive Function in Migraine - J Gordon Millichap (Pediatric Neurology Briefs, 2010)
Researchers at the Johnson & Johnson Pharmaceutical Research & Development, New Jersey and Belgium, and University of California, Los Angeles, CA used the Cambridge Neuropsychological Test Automated Battery (CANTAB) and cognitive adverse events to evaluate neurocognitive effects of topiramate 100 mg/day vs placebo in 70 migraine patients aged 12 through 17 years.